Economic Evaluation of Cerebral Palsy in a Resource-challenged Setting - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Cerebral palsy is a problem with a high prevalence in Africa and requires a life-long care. It is associated with high treatment cost and disruptions in the social life of caregivers.Aims:To evaluate the costs of care among some selected children with cerebral palsy in the resource-challenged setting.Settings and Design:A cross-sectional study.Materials and Methods:Prevalencebased costs were stratified by patients’ socio-demographic characteristics and socioeconomic scores (SES). The “bottom-up” and “human capital” approaches were used to generate estimates on the direct and indirect costs of 100 patients with cerebral palsy.Statistical analysis used:All estimates of the financial burden of cerebral palsy were analyzed from the “patients’ perspective” using IBM SPSS statistics software, version 23.Results:Onehundred children aged between 6 and 180 months were recruited, 62.0% males and 38.0% females with a male to female ratio of 1.6:1. The majority (79.0%) resides in an urban setting and 45.0% are within low socioeconomic class (Ogunlesi SES IV and V). The total cost of cerebral palsy care per month was N3,702,612.6 (10,285.04) with a mean cost per patient per month of N37,026.1 (102.85). The total direct cost of care per month was 77% of the total monthly cost, while the indirect cost per month was 23%. Medications/drugs are the principal cost drivers, comprising approximately 45.0% of the total direct costs per month. The total annual cost was N44,431,351.2 (123,420.42) with a mean yearly cost per patient of N444,313.5 (1,234.20).Conclusions:The study provided a preliminary estimate of the high cost of care borne by the family in the treatment of childhood cerebral palsy. The indirect cost is the principal cost driver of the total cost incurred by the family..